2020
DOI: 10.4012/dmj.2018-291
|View full text |Cite
|
Sign up to set email alerts
|

Repair bond strength of bulk-fill resin composite: Effect of different adhesive protocols

Abstract: This study evaluated the effect of different adhesive protocols on the shear bond strength (SBS) of bulk-fill resin composite repaired with bulk-fill or conventional composite. Cylindrical bulk-fill resin composite specimens were prepared and allocated into groups according to the bonding strategy: no treatment, Silane+Scotch Bond Multipurpose (S+SBMP), Tetric N Bond Universal, and Single Bond Universal. Following bonding strategy, bulk-fill or conventional composite buildups were performed. After 24 h of stor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 18 publications
2
28
1
3
Order By: Relevance
“…After surface treatment to increase the roughness, the silane coupling agent has been usually used as bonding agent, in order to improve the adhesion between the filler particles and organic matrix of aged and new resin composite, because it is a bifunctional molecule capable of to bind with carbon double bonds of organic matrix by non-hydrolyzable functional group and hydroxyl groups of inorganic phase by hydrolyzable alkoxy groups (Fornazari et al, 2017). However, the benefit of using silane is controversial, as some studies (Ferracane, 2011;Tantbirojn et al, 2015;Fornazari et al, 2017;Cuevas-Suárez et al, 2020) reported the increase on bond strength of composite repairs, while others (Cho et al, 2013;Lima et al, 2014) showed no difference in use or not of this bifunctional coupling agent.…”
Section: Discussionmentioning
confidence: 99%
“…After surface treatment to increase the roughness, the silane coupling agent has been usually used as bonding agent, in order to improve the adhesion between the filler particles and organic matrix of aged and new resin composite, because it is a bifunctional molecule capable of to bind with carbon double bonds of organic matrix by non-hydrolyzable functional group and hydroxyl groups of inorganic phase by hydrolyzable alkoxy groups (Fornazari et al, 2017). However, the benefit of using silane is controversial, as some studies (Ferracane, 2011;Tantbirojn et al, 2015;Fornazari et al, 2017;Cuevas-Suárez et al, 2020) reported the increase on bond strength of composite repairs, while others (Cho et al, 2013;Lima et al, 2014) showed no difference in use or not of this bifunctional coupling agent.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, the two most commonly used laboratory methods were the bond strength and the examination of fractured surface using stereo-or Scanning Electron Microscopes. (15)(16)(17) Nano-leakage is another way to evaluate the quality of the repair interface, which depends on tracing of silver nitrate particles along the composite-composite interface. (12)(13)(14) The advantage of nano-leakage methodology was that this method could be able to detect even the early signs of poor composite-composite interface quality, yet the repair bond strength was not affected.…”
Section: Introductionmentioning
confidence: 99%
“…New composite may be adhered to aged composite through micromechanical interlocking to irregularities in the prepared surface and through chemical bonding to the filler particles and the organic matrix. 12,13,14 Bonding agents improve the chemical bonds between the old and new materials. Silanes increase surface wetting, thereby enhancing diffusion of the bonding agent into the substrate.…”
Section: Introductionmentioning
confidence: 99%